2020
DOI: 10.3390/agronomy10101460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agronomic Biofortification with Zinc on the Nutrient Content, Bioactive Compounds, and Antioxidant Capacity of Cowpea Bean (Vigna unguiculata L. Walpers)

Abstract: Zinc intake deficiency is a public health problem and increasing the nutrient’s content in the edible parts of plants can help mitigate it. The objective of this work was to determine the effect of the edaphic and foliar application of zinc sulphate on the nutrient content, bioactive compounds, and antioxidant capacity of cowpea beans (Vigna unguiculata L. Walpers). A sample of 100 grains was taken, and the length, width, thickness, weight, ash content, fat, humidity, fibers, carbohydrates, protein, energy, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…Ash corresponds to mineral content, and this indicates that the mineral content of wheat was improved after application of zinc fertilizer. This is in line with the conclusion that fertilization increased ash content compared with the control [ 16 ]. Compared with LT2, LZ2 exhibited no significant difference in the ash content of B flour and R flour, but decreased content of ash in fine bran.…”
Section: Resultssupporting
confidence: 91%
“…Ash corresponds to mineral content, and this indicates that the mineral content of wheat was improved after application of zinc fertilizer. This is in line with the conclusion that fertilization increased ash content compared with the control [ 16 ]. Compared with LT2, LZ2 exhibited no significant difference in the ash content of B flour and R flour, but decreased content of ash in fine bran.…”
Section: Resultssupporting
confidence: 91%
“…This may explain the increase in the antioxidant activity of the plant by the foliar application of zinc sulfate [56]. The foliar application of Zn increased phenol, flavonoids and the antioxidant activity of cowpea [57]. The essential oil yield of essential oil-bearing plants depends on the drug yield and essential oil content.…”
Section: Phytochemical Evaluation and Antioxidant Activitymentioning
confidence: 99%
“…The seed priming with Mo increased the grain yield and net return in chickpea [ 22 ]. However, many studies have reported the sole application of biofertilizers in cowpea [ 23 , 24 ] but a comparative analysis of the effect of foliar application, seed priming and soil treatment using Mo, Zn and Fe along with their interactive effects on cowpea has not been explored so far. This interactive effect could be better explored in terms of micronutrient accumulation in grain and stover along with the improvement in crop quality which could benefit human health by combating hidden hunger.…”
Section: Introductionmentioning
confidence: 99%